Distal Radius Fracture: A Systematic Review of Observational Studies (London Journal of Medical and Health Research, 2023)
The purpose of this research is to analyze prevalence and incidence studies on the seasonality of trauma epidemiology with regard to distal radius fractures through a systematic review, in which cross-sectional and longitudinal studies were selected regarding the analysis of clinical and epidemiological variables associated with fractures of the distal radius. For this, MEDLINE®, LILACS, SCIELO and PUBMED platforms were used. From a total of 45,634 articles, after applying the inclusion and exclusion criteria, 18 scientific publications were eligible among the 64 read in full. According to the review, it appears that there is seasonality in distal radius fractures according to  he seasons of the year. The decreased bone strength of these patients was associated with an increased risk of fracture in 10 years and individuals from a rural environment with less hospital support have a greater chance of not having an adequate post fracture follow-up.
Keywords: distal radius fractures; observational studies; cross-sectional studies; longitudinal studies